How peace corps volunteers influence the United States: an analysis based on pragmatism - Long Ye; Zhihua Liao; Yuyuan Yuan (Trans/Form/Ação, 2023)
From the perspective of pragmatic diplomatic philosophy, Peace Corps can benefit the United States, which is an important reason for the domestic support it receives within the United States. Through the volunteers’ acculturation experience, cultural exchanges between the United States and host countries are promoted and the awareness of the American society about the Third World countries is raised, which is the true value of the Peace Corps from the perspective of American interests. As members of American society, Peace Corps volunteers gain a comprehensive and in-depth understanding of the Third World in their host countries, which is not only an important part of improving the awareness of the American society the Third World, but is also an important bridge to spread this awareness in the United States. When volunteers return to the United States after finishing their service, they bring their understanding of the Third World to different industries and fields in American domestic society. Among them, American education and diplomacy are mostly affected. These are of great significance in improving the international vision and awareness of American education and the reliability of American foreign policy.